The effectiveness of a proposed strategy based on Matthew Lipman’s mental theory in Achievement of 4th students in measurement and Evaluation - Mohammed Al Zubaidy, Raad Khalaf (Journal of Tikrit University for Humanities, 2024)
The present research aims at building a proposed strategy based on Matthew Lipman’s mental theory. The effectiveness of the proposed strategy, based on Matthew Liebman’s mental theory, on the achievement of students in measurement and calendars. The researcher used the descriptive approach to build the proposed strategy and the experimental approach to determine the effectiveness of the proposed strategy, which was based on Matthew Liebman’s mental theory and applied to a sample of 100 students from the Technical Education Department, which was distributed among the first two pilot groups studying the proposed strategy and the second female officer studying the traditional method. After applying the strategy and processing the study data, the study reached the following conclusions: The students of the pilot group who studied in accordance with the proposed strategy based on Matthew Liebman’s strategy outstripped the students of the commanding group who studied using the traditional method of the collection test. Based on the results of the statistical analysis that showed the pilot group’s superiority over the control group, the alternative hypothesis was accepted, which states that "there is a statistically significant difference at the level of an indication (0.05) in terms of the average scores of the experimental group and the officer in the collection test and for the pilot group that was studied in accordance with the proposed strategy based on Matthew Liebman’s mental theory. The researcher concluded: The effectiveness of the proposed strategy based on Matthew Liebman’s mental theory on the students of the pilot group compared to the traditional way in which the students’ work of mind and knowledge arbitration worked in order to complete their understanding of the subjects considered. The study identified the need to provide students with appropriate opportunities to exercise their mental abilities by providing students with learning experiences linked to their reality and by giving them sufficient time to provide learning environments conducive to these ends. The study suggested that those theories should be used in the field of teaching, in particular cognitive learning theories and theories that promote the work of the educated mind in teaching